EXRAORDINARY COMITTEE’S INQUIRY AGAINST SIMA MILUTINOVIĆ SARAJLIJA - Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The aricle sheds light on the inquiry of Extraordinary Committee, formed in 1840 by prince Mihailo Obrenović (1839–1842, 1860–1868) and his partisans from State Council in order to examine political crimes committed by their opposition, so-called constitution-defenders. Having examined archival materials, the author showed for what time the inquiry lasted, in what phases it can be divided, what sorts of evidence were collected and the facts about Milutinović’s activities that they revealed. The inquiry can be divided into two major phases. During the first of these phases, the subject of investigation was the report of Jevrem Obrenović, president of the State Council, of May 7th 1840 alleging Milutinović offended the prince and his family. This part of inquiry was conducted by other state bodies, on request of Extraordinary Committee and following its instructions. Information on Milutinović’s offense were collected via documentary evidence and testimonies of witnesses. In the second phase, Extraordinaty Committee itself examined Milutinović’s defamations against the prince, spoken before the bookshop of renowned bookseller Gligorije Vozarović in March 1840 and on the occassion of rebellion in Kolubara District in June 1840. Extraordinary Committee learned information about Milutinović’s activities through testimonies of witnesses and their confrontation. The decision of Extraordinary Committee in Milutinović’s case can not be found in archive materials. They do not contain a sort of resolution, stating whether collected evidence provide necessary material for trial against the suspect or not, issued in all other Extraordinary Committee’s inquiries. As archive material also fail to provide some of other significant documents, whose existence is mentioned in the acts of inquiry, it seems probable that the resolution was indeed issued, but lost in a later period. Therefore, detecting a trace which could lead to this document is an imperative for future researcher who wants to form a judgment about inquiry against Milutinović.